2017
DOI: 10.1155/2017/5387913
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Phosphatidylcholine Species in Superficial-Type Pharyngeal Carcinoma

Abstract: Objectives. Superficial-type pharyngeal squamous cell carcinoma (STPSCC) is defined as carcinoma in situ or microinvasive squamous cell carcinoma without invasion to the muscular layer. An exploration of the biological characteristics of STPSCC could uncover the invasion mechanism of this carcinoma. Phosphatidylcholine (PC) in combination with fatty acids is considered to play an important role in cell motility. Imaging mass spectrometry (IMS) is especially suitable for phospholipid analysis because this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This suggests that parotid cancer tissue has a markedly different phospholipid composition compared to that of non-tumor tissue. Alterations in the lipid composition of tissues have been reported in several cancers, including breast cancer [ 18 , 21 ], prostate cancer [ 17 , 19 ], lung cancer [ 22 ], kidney cancer [ 23 ], pharyngeal cancer [ 24 ], and oral cancer [ 20 , 25 , 26 ]. Furthermore, it has been suggested that these specific lipid profiles vary from among carcinomas, and may be potential diagnostic, prognostic, and predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that parotid cancer tissue has a markedly different phospholipid composition compared to that of non-tumor tissue. Alterations in the lipid composition of tissues have been reported in several cancers, including breast cancer [ 18 , 21 ], prostate cancer [ 17 , 19 ], lung cancer [ 22 ], kidney cancer [ 23 ], pharyngeal cancer [ 24 ], and oral cancer [ 20 , 25 , 26 ]. Furthermore, it has been suggested that these specific lipid profiles vary from among carcinomas, and may be potential diagnostic, prognostic, and predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Most transferosomes contain phosphatidylcholine (C18) as the lipid fraction (usually above 70%) as it is the most abundant lipid component of the cell membrane, and hence, it is highly tolerated for the skin, decreasing the risk of undesirable effects, such as hypersensitivity reactions (Ishikawa et al, 2017). Soya phosphatidylcholine (>95 % purity) is a GRAS (Generally Regarded As Safe) excipient and actually it has been used in suspensions, emulsions, mixed micelles, solid dispersions and drug-phospholipid complexes with a good safety profile (Rajan et al, 2011;van Hoogevest and Wendel, 2014).…”
Section: Transferosomes In Preclinical Studies -Laboratory Scale Prepmentioning
confidence: 99%